Rituximab Therapy for Primary Sjögren’s Syndrome - Chen, Yi Han; Wang, Xin Yu; Jin, Xin; Yang, Zi; Xu, Jianguang (Frontiers in Pharmacology, 2021)
Primary Sjögren’s syndrome (pSS) is among the most common systemic autoimmune diseases of the connective tissues, characteristic of the presentation of keratoconjunctivitis sicca and xerostomia. A cardinal feature of the pathogenesis of SS is B-cell hyperactivity, which has invited efforts on optimal B-cell targeted therapy, whereas conventional corticosteroids and disease-modifying antirheumatic drugs (DMARDs) are restricted to symptomatic relief. As per the first EULAR recommendation for pSS patients published in 2020, regimens with monoclonal antibodies targeting B cells may be initiated in patients with severe, refractory systemic disease, notably rituximab (RTX), a mouse-derived monoclonal antibody that targets CD20 antigen and contributes to B-cell depletion. Nonetheless, the data available from clinical trials with RTX are often controversial. Despite the lack of promising results from two large RCTs, several positive clinical efficacies were demonstrated. This current review analyzed the efficacy and safety of clinical trials available and elucidated the potential effects of RTX on the immune system, especially B and T cells. Furthermore, plausible explanations for the discrepancy in clinical data were also presented.